2016
DOI: 10.1292/jvms.15-0635
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the renal dimensions in captive tigers

Abstract: Ultrasonographic measurements of kidney size are useful in the practical diagnosis of kidney diseases in animals. In tigers, there is a lack of information regarding the ultrasonography methods used to measure the kidney size of the tiger. Thirty-three healthy captive tigers (Panthera tigris) were placed in lateral recumbency for ultrasonography. The measurements obtained from the ultrasonography were computed, and the results showed that there was a statistically significant difference between genders in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Lauder et al [7] demonstrated that the right main renal artery was longer than the left, but the left renal artery had a greater diameter in patients with hypertension. There is significant difference between right and left kidney length among schoolage children [8] and nondiabetic patients without CKD [9]. In a study performed by Ito et al [10], the differences in apparent diffusion coefficient (ADC) values of each kidney during different cardiac phases were compared.…”
mentioning
confidence: 99%
“…Lauder et al [7] demonstrated that the right main renal artery was longer than the left, but the left renal artery had a greater diameter in patients with hypertension. There is significant difference between right and left kidney length among schoolage children [8] and nondiabetic patients without CKD [9]. In a study performed by Ito et al [10], the differences in apparent diffusion coefficient (ADC) values of each kidney during different cardiac phases were compared.…”
mentioning
confidence: 99%